Impact of Automatic Promotion on the Academic Performance of Learners in Selected Primary Schools of Bubiita Subcounty, Bududa District - Wambele Karim (Uganda Christian University, 2024)
The study was about the “impact of automatic promotion on the academic performance of learners in selected primary schools in Bubiita sub-county Bududa District. The study was guided by the following objectives; to find out the extent to which automatic promotion policy is being implemented in Bubiita; to establish the effect of automatic promotion policy on academic performance in Bubiita sub-county; to establish the measures to improve performance. The study used a descriptive research design. Data was collected from 152 respondents using self-administered questionnaires with both quantitative and qualitative methods. Objective one found out that the extent to which automatic promotion policy was implemented in Uganda was great. Respondents confirmed that automatic promotion demotivates learners. This was leading by 60(39.5%) respondents, followed by the assertion that all learners are promoted to the next class by 40(26.4%), automatic promotion leads to poor grades 30(19.7%), automatic promotion leads to increased dropout which was proposed by 16(10.5%) and that automatic promotion leads to overcrowded classes which was proposed by 06(3.9%). Objective two of the study found out that automatic promotion negatively affects the learner’s future socially and academically which was leading by 58(38.2%), this was followed by the fact that automatic promotion reduces the power of teachers 44(28.9%), automatic promotion does not differentiate between the bright and the dull learners which was proposed by 30(19.7%), 17(11.2%) of the respondents said that automatic promotion lowers the quality of education with 03(02%) of the respondents affirming that automatic promotion policy is for the next class. Objective three of the study revealed that much as automatic promotion affects the academic performance of learners, involvement of both parents and teachers which was proposed by 52(34.2%) was the leading remedy which was followed by health status of the learners 38(25%), this was followed by promoting the children on merit 30(19.7%) , abolishing the automatic promotion policy by 22(14.5%) and creating awareness which was supported by10(6.6%). The study concluded that the extent to which automatic promotion is implemented teachers’ effects of automatic promotion and the measures to improve academic performance in the selected primary schools are serious variables that affect learners’ performance, teachers’ performance and need to be addressed. The study recommended that school administrators sensitize parents on the dangers of automatic promotion in order for them to take right decisions.